Trading for Status. (1st August 2014) - Hong, Harrison; Jiang, Wenxi; Wang, Na; Zhao, Bin
Abstract : We show that Keeping-Up-with-the-Joneses preferences can explain several puzzling retail investor behaviors, including the excessive trading of small local stocks. Status concerns lead households, especially those living in affluent areas, to demand these stocks to track their neighbors' wealth. This demand varies procyclically with the stock market's value and generates household trading. Using Chinese data on local stock turnover, stock message boards, and brokerage account trading, we test and confirm this hypothesis by exploiting the uneven rise of affluence across Chinese cities between 1998 and 2012.